TWEAK/Fn14 Drives Tumor Progression and Is Associated With Poor Survival of Colorectal Liver Metastases With Replacement Growth Patterns - Naoki Matsuyama; Takanori Konishi; Tsukasa Takayashiki; Shigetsugu Takano; Daisuke Suzuki; Nozomu Sakai; Isamu Hosokawa; Takashi Mishima; Kensuke Suzuki; Hitoe Nishino; Shinichiro Nakada; Masayuki Ohtsuka (Cancer Medicine, 2025)
ABSTRACT Objective Colorectal liver metastases (CRLMs) with replacement growth pattern (rHGP) are associated with a poor prognosis; however, the underlying mechanisms driving rHGP remain poorly understood. This study investigated the effect of the TWEAK/Fn14 axis in CRLMs on tumor progression to explore the pathology of CRLMs with rHGP. Method In total, 129 patients with CRLMs who underwent curative resection were investigated. Results Patients with rHGP had significantly poor overall survival after surgery than those with other growth patterns. CRLMs with rHGP exhibited epithelial‐mesenchymal transition (EMT) activation and a distinct immune microenvironment. We focused on TWEAK/Fn14 axis to clarify the mechanism by which the tumor microenvironment affects tumor progression in CRLMs with rHGP. TWEAK was expressed in the tumor microenvironment, accompanied by the infiltration of Th17 cells and M2 macrophages, whereas Fn14 was expressed in cancer cells within CRLMs. High TWEAK/high Fn14 expression in CRLMs was more frequently observed in CRLMs with rHGP and was associated with a worse prognosis. This was accompanied by high grade of tumor budding and poorly differentiated clusters in CRLMs, and increased risk of extrahepatic metastases. In vitro, recombinant TWEAK (100 ng/mL) induced phosphorylation of IκB and NFκB (p65) and also enhanced cell migration, invasion, and EMT maker expression in colorectal cancer cells. Cell migration and invasion enhanced by recombinant TWEAK were suppressed by an Fn14 antagonist (ITEM‐4: 200 ng/mL). Discussion This study clarified that the TWEAK/Fn14 axis in CRLMs promotes invasiveness and metastatic potential, leading to poor prognosis. It may be crucial in the adverse survival outcomes of CRLMs with rHGP.